Genetic and Epigenetic Studies in Diabetic Kidney Disease - Gu, Harvest F. (Frontiers in Genetics, 2019)
Kidney disease is a worldwide health crisis, while diabetes kidney disease (DKD) has become a leading cause of end stage renal disease (ESRD). DKD is a microvascular complication and occurs in 30-40% of diabetes patients. Epidemiological investigation and clinical observation on the familial clustering and heritability in DKD have implicated that genetic susceptibilities are involved in the pathogenesis. Furthermore, DKD is a progressive and long-term complication, in which epigenetic effects and environmental factors are interacted with the genetic background. In recent years, researchers have put efforts in genetic and epigenetic studies of DKD in order to better understand its molecular mechanisms. In this review, clinical material, research approach and experimental design that have been used for genetic and epigenetic studies of DKD are described. Current information from genetic and epigenetic studies of DKD and ESRD in patients with diabetes, including the approaches of genome or epigenome-wide association study (GWAS or EWAS) and candidate gene association analysis, is summarized. Further investigation of molecular defects in DKD with new approaches such as next generation sequencing analysis and phenome-wide association study (PheWAS) is discussed.